2013
DOI: 10.1371/journal.pone.0058590
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Trends in Community HIV Viral Load in Barbados: Implications for Treatment as Prevention

Abstract: BackgroundTreatment as prevention is a paradigm in HIV medicine which describes the public health benefit of antiretroviral therapy (ART). It is based on research showing substantial reductions in the risk of HIV transmission in persons with optimally suppressed HIV-1 Viral Loads (VL). The present study describes ten year VL trends at the national HIV treatment unit and estimates VL suppression at a population level in Barbados, a Caribbean island with a population of 277,000, an estimated adult HIV prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Multiple studies have shown that many infected individuals start controlling their behaviors likely to transmit infection to sex or needle-sharing partners once they are aware of their positive HIV status [ 7 11 ]. As antiretroviral treatment (ART) lowers HIV viral load and thus reduces the risk for transmission to others [ 12 14 ], early referral to medical care and early ART could prevent HIV transmission in communities while reducing a person's risk for HIV-related illness and death. In addition, voluntary HIV counseling and testing (VCT) is an important entry point to other HIV/AIDS services, including prevention of mother-to-child transmission (PMTCT), prevention and management of HIV-related illnesses, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that many infected individuals start controlling their behaviors likely to transmit infection to sex or needle-sharing partners once they are aware of their positive HIV status [ 7 11 ]. As antiretroviral treatment (ART) lowers HIV viral load and thus reduces the risk for transmission to others [ 12 14 ], early referral to medical care and early ART could prevent HIV transmission in communities while reducing a person's risk for HIV-related illness and death. In addition, voluntary HIV counseling and testing (VCT) is an important entry point to other HIV/AIDS services, including prevention of mother-to-child transmission (PMTCT), prevention and management of HIV-related illnesses, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…All HIV-infected persons receive their inpatient care at Queen Elizabeth Hospital and ambulatory care is provided by a centralized HIV clinic that has operated from Ladymeade Reference Unit since 2002 (Kumar et al 2006). The Ladymeade Reference Unit was established as part of the Government's expanded response to the HIV epidemic and consists of a clinic, inhouse pharmacy and an internationally accredited laboratory (Kumar et al 2006;Landis et al 2013). Queen Elizabeth Hospital is the only public hospital in Barbados, providing more than 95% of all inpatient care to the population (Kumar et al 2007).…”
Section: Hiv Care In the Caribbeanmentioning
confidence: 99%
“…The importance of VL suppression as a public health tool in the fight against HIV transmission cannot be overstated. The Caribbean has earned praise from UNAIDS for recording decreasing trends in new infections [ 22 ], with strong gains recorded in prevention of mother to child transmission (PMTCT) and treatment as prevention programs [ 18 ; 23 ; 24 ]. Declining infection rates are likely to be underpinned by the prevention benefits of ART, recognized by the WHO consolidated guidelines and the regional PAHO M & E framework that identifies viral load as the key metric for evaluating patient engagement in the continuum of care [ 13 ; 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this threshold value, the CDC estimated 28% of the HIV infected population in the USA had optimally suppressed VL [ 17 ]. By the same methodology, viral suppression in Barbados was 26% of the HIV infected population [ 18 ]. Similar information is not available from other Caribbean countries, partly because of logistical challenges in VL testing.…”
Section: Introductionmentioning
confidence: 99%